Non-Fragile Observer-Based Quantized Control for a Class of One-Sided Lipschitz Systems - Acosta-Barbosa, K; Zoulagh, T (Elsevier B.V., 2022)
The topic of nonfragile observer design for a class of one-sided Lipschitz nonlinear systems with quantized inputs is investigated in this study. The one-sided Lipschitz and quadratically inner-bounded conditions were used to obtain less conservative synthesis requirements for the observer design. Sufficient conditions, stated in terms of linear matrix inequalities, are supplied using auxiliary variables and a decoupling method to ensure the resilience of the quantized closed-loop. The controller and observer gains may then be found in the same process. An example generated from a nonlinear DC motor model is provided to demonstrate the efficiency of the suggested technique. © 2022 Elsevier B.V.. All rights reserved.